Fine needle aspiration cytology of lymph node in erythema nodosum leprosum: A case report with review of literature - Bhagyashri R Hungund; Sujata R Dafale; Ranjit Kangle; Ramesh Y Chavan; Ganga S Pilli (Wolters Kluwer Medknow Publications, 2014)
The acute manifestations and subsequent complications call for early recognition and management of erythema nodosum leprosum (ENL). Its diagnosis is conventionally based on skin biopsy and slit skin smears. Fine needle aspiration cytology (FNAC) has been found to be a simple and useful tool in the diagnosis of this entity. Lymphadenopathy is a known manifestation of leprosy and its reactions. The present case is reported to underscore the importance of FNAC of lymph node in diagnosis of ENL. A 39-year-old male, known case of lepromatous leprosy on treatment, presented with fever, joint pains, raised lesions all over the body and enlarged bilateral inguinal lymph nodes. FNA of the lymph node revealed characteristic features of ENL. FNA of lymph nodes is simple, non-invasive, useful tool in early diagnosis of ENL.